Globalization, Music and Cultures of Distinction The Rise of Pop Music Criticism in Italy - Varriale, Simone; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book is the first comprehensive account of how Anglo-American popular music transformed Italian cultural life. Drawing on neglected archival materials, the author explores the rise of new musical tastes and social divisions in late twentieth century Italy. The book reconstructs the emergence of pop music magazines in Italy and offers the first in-depth investigation of the role of critics in global music cultures. It explores how class, gender, race and geographical location shaped the production and consumption of music magazines, as well as critics' struggle over notions of expertise, cultural value and cosmopolitanism. Globalization, Music and Cultures of Distinction provides an innovative framework for studying how globalization transforms cultural institutions and aesthetic hierarchies, thus breaking new ground for sociological and historical research. It will be essential reading for scholars and students interested in cultural sociology, popular music, globalization, media and cultural studies, social theory and contemporary Italy.
Introduction: How Things Come Into Being -- Part I: Situating the Study -- 1. New Forms of Distinction, New Cultural Institutions -- 2. Globalization and Artistic Legitimation: Reconceptualizing Bourdieu -- Part II: Pop Music Criticism in Italy (1969-1977) -- 3. Young, Educated and Cosmopolitan: A New Cultural Institution -- 4. Economic Cosmopolitanism: The Case of Ciao 2001 -- 5. Political Cosmopolitanism: The Case of Muzak and Gong -- Part III: Evaluating Music and Music Criticism -- 6. Aesthetic Encounters: Evaluating Rock, Jazz and Soul -- 7. Music Magazines as Alternative Public Spheres -- Conclusion: The Struggle Goes On < .
Keywords: Globalization; Social Structure, Social Inequality